The Phytosterol Peniocerol Inhibits Cell Proliferation and Tumor Growth in a Colon Cancer Xenograft Model - Couder-García, Beatriz del Carmen; Jacobo-Herrera, Nadia J.; Zentella-Dehesa, Alejandro; Rocha-Zavaleta, Leticia; Tavarez-Santamaría, Zaira; Martínez-Vázquez, Mariano (Frontiers in Oncology, 2019)
Abstract Objective. This study aimed to evaluate the cytotoxic activity of peniocerol against human colon cancer cell lines and its antitumor effect in vivo in a xenograft model using nu/nu mice. Materials and methods. SW-620, HCT-15, and HCT-116 colon cancer cell lines were treated with peniocerol (10 to 80 µM) for 24, 48 or 72 hours, the number of cells was assessed by the violet crystal assay. Cell apoptosis induction was detected by flow cytometry with the Annexin-V FLUOS/PI kit. The potential toxicity of peniocerol was evaluated in nu/nu mice. Antitumor activity of peniocerol in vivo was evaluated in a xenograft model of HCT-116 in nu/nu mice. After treatment, the effect of peniocerol was analyzed in histological sections of tumors by immunohistochemistry using DAPI and anti-PCNA antibodies. Results. Peniocerol inhibited cell growth and induced apoptosis in vitro in a time and dose-dependent manner. Besides, peniocerol administration (30 mg/kg or 15 mg/kg) inhibited tumor growth in the xenograft mice. Conclusions. Our results proved that peniocerol inhibits cell proliferation and induces apoptosis in vitro and in vivo. Anti tumor